Altered functioning of reward circuitry in youth offspring of parents with bipolar disorder. Issue 1 (16th September 2015) - Manelis, A.; Ladouceur, C. D.; Graur, S.; Monk, K.; Bonar, L. K.; Hickey, M. B.; Dwojak, A. C.; Axelson, D.; Goldstein, B. I.; Goldstein, T. R.; Bebko, G.; Bertocci, M. A.; et al.
Abstract : Background: Offspring of parents with bipolar disorder (BD) (BO) are at higher risk of BD than offspring of parents with non-BD psychopathology (NBO), although both groups are at higher risk than offspring of psychiatrically healthy parents (HC) for other affective and psychiatric disorders. Abnormal functioning in reward circuitry has been demonstrated previously in individuals with BD. We aimed to determine whether activation and functional connectivity in this circuitry during risky decision-making differentiated BO, NBO and HC. Method: BO ( n = 29; mean age = 13.8 years; 14 female), NBO ( n = 28; mean age = 13.9 years; 12 female) and HC ( n = 23; mean age = 13.7 years; 11 female) were scanned while performing a number-guessing reward task. Of the participants, 11 BO and 12 NBO had current non-BD psychopathology; five BO and four NBO were taking psychotropic medications. Results: A 3 (group) × 2 (conditions: win-control/loss-control) analysis of variance revealed a main effect of group on right frontal pole activation: BO showed significantly greater activation than HC. There was a significant main effect of group on functional connectivity between the bilateral ventral striatum and the right ventrolateral prefrontal cortex ( Z > 3.09, cluster- p < 0.05): BO showed significantly greater negative functional connectivity than other participants. These between-group differences remained after removing youth with psychiatric disorders and psychotropic medications from analyses. Conclusions: This is the first study to demonstrate that reward circuitry activation and functional connectivity distinguish BO from NBO and HC. The fact that the pattern of findings remained when comparing healthy BO v . healthy NBO v . HC suggests that these neuroimaging measures may represent trait-level neurobiological markers conferring either risk for, or protection against, BD in youth.